Learning & Innovation dalam Pengembangan Sumber Daya Manusia yang Unggul dan Kompetitif di SMP Sahara - Ramdani Bayu Putra; Rio Andhika Putra; Hasmaynelis Fitri (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2022)
The development of human resources (HR) is an important factor in the world of education. Through formal and non-formal education students are formed with good knowledge and skills, which later students have the ability to be creative or produce creativity in the form of innovation in the application of a particular knowledge or skill in supporting student learning at school. As the next generation of the nation, students are educated with various knowledge and expertise and with existing competencies, which will be able to fill the needs of the world of work and the world of business that are superior and competitive. Community service activities (PKM) are one of the Tridharma of Higher Education which must be carried out by Lecturers in accordance with Education Law No. 12 of 2012. This PKM activity was carried out with the aim of contributing to the improvement of Sahara Middle School students who are at Jalan Padang Pasir No 30 Padang, West Padang District, Padang City. Through this activity, students are expected to be able to increase learning & innovation as the nation's next generation who have excellence and are competitive in their fields in the future